1979
DOI: 10.1111/j.1570-7458.1979.tb02861.x
|View full text |Cite
|
Sign up to set email alerts
|

The Insecticidal Activity of Some Norditerpene Dilactones

Abstract: The effects on housefly (Musca domestica) of six norditerpene lactones (nagilactones B, D, E, podolide, hallactone B and 14‐epi‐ponalactone A) in a defined diet were tested. Nagilactone D was the most active, with an LD50 of 0.7 ppm. Nagilactones C and D were also toxic to light‐brown apple moth (Epiphyas postvittana) and codling moth (Laspeyresia pomonella). The relationship between lactone structure and toxicity to housefly is discussed. ZUSAMMENFASSUNG INSEKTIZIDWIRKUNG VON NORDITERPENLACTONEN Viele aus Pod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…One of the two angular methyl groups in NB is subjected to a pronounced shielding due to the y-effect of the hydroxyl group at C-1 (this is also the case in other type A, dilactones 1, 8 and 10). Thus, the methyl resonance at 618.7 in 3 is assigned to C-20, leaving the methyl carbon signal at 624.0 to C-18.…”
Section: Type a Dilactonesmentioning
confidence: 94%
“…One of the two angular methyl groups in NB is subjected to a pronounced shielding due to the y-effect of the hydroxyl group at C-1 (this is also the case in other type A, dilactones 1, 8 and 10). Thus, the methyl resonance at 618.7 in 3 is assigned to C-20, leaving the methyl carbon signal at 624.0 to C-18.…”
Section: Type a Dilactonesmentioning
confidence: 94%
“…colorless needles (CHCl 3 /hexane); mp 194–195 °C (lit 191–193 °C);32 [α]26 D -272.1 ( c 0.53, CHCl 3 :CH 3 OH 9:1) (lit. −332.7);32 UV (CH 3 OH) λ max (log ε) 260 (4.21); CD (CH 3 OH) [θ] 296 -5.1.…”
Section: Methodsmentioning
confidence: 99%
“…With the scattered occurrence of the different podolactone-type inhibitors (Sasse et al 1981) the question arises as to their biological role. Cartwright et ai (1977) and Kato et al (1977) have identified momilactone B as a phytoalexin as well as a plant-growth inhibitor and Ito and Kodama (1976) and Singh et al (1979) suggested that podolactones protect against predation by insects. Brown and Sanchez L. (1974) have also suggested that they are possible allelopathic agents though this seems unlikely (Sasse et al 1981) even though they can delay germination.…”
Section: Floweringmentioning
confidence: 99%